2017
DOI: 10.4315/0362-028x.jfp-16-517
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Inactivation of Listeria monocytogenes and Salmonella during Water and Steam Blanching of Vegetables

Abstract: Thermal inactivation of Listeria monocytogenes and Salmonella was evaluated on peas, spinach, broccoli, potatoes, and carrots that were treated with hot water and steam. One gram-positive bacterium, L. monocytogenes, and one gram-negative bacterium, Salmonella, were selected as pertinent human pathogens for evaluation. Samples were inoculated with a composite of five strains each of L. monocytogenes and Salmonella to achieve approximately 10 to 10 CFU/g. Inoculated samples were treated with hot water at 85 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…L. monocytogenes was reduced more than 5 log 10 within 1 min on carrot, spinach, peas and broccoli by steam blanching at 96.7°C. The study by Ceylan et al (2017) revealed that shorter t/T treatment is applicable when using hot water blanching. However, either hot water or steam blanching can achieve the desired 5 log 10 reduction in L. monocytogenes when adequate t/T combinations are applied.…”
Section: Blanchingmentioning
confidence: 99%
“…L. monocytogenes was reduced more than 5 log 10 within 1 min on carrot, spinach, peas and broccoli by steam blanching at 96.7°C. The study by Ceylan et al (2017) revealed that shorter t/T treatment is applicable when using hot water blanching. However, either hot water or steam blanching can achieve the desired 5 log 10 reduction in L. monocytogenes when adequate t/T combinations are applied.…”
Section: Blanchingmentioning
confidence: 99%
“…Common blanching temperatures range from 70 to 100ºC for a few minutes, whereas steam blanching requires applying steam for longer time period (Ceylan et al, 2017). Common blanching temperatures range from 70 to 100ºC for a few minutes, whereas steam blanching requires applying steam for longer time period (Ceylan et al, 2017).…”
Section: Blanchingmentioning
confidence: 99%
“…However, longer treatment times and higher temperatures were required for steamblanching compared to hot water blanching (Ceylan et al, 2017). peas, spinach, broccoli, potatoes and carrots) were inoculated with approximately 10 8 -10 9 CFU/g L. monocytogenes and Salmonella, respectively and treated with hot water at 85 and 87.8ºC and steam at 58 and 96.7ºC for up to 3.5 min.…”
Section: Blanchingmentioning
confidence: 99%
See 2 more Smart Citations